UPAYA GURU BIMBINGAN DAN KONSELING DALAM MENCEGAH PRILAKU MENYIMPANG SISWA DI SEKOLAH - Ifnaldi (Sekolah Tinggi Ilmu Tarbiyah (STIIT) Ahlussunnah Bukittinggi, 2017)
Guidance and councelling service is supposed to achievemend education andrealization of councelling purpose. Preventive function is guidance andcouncelling fuction that has relation with councellor efforts to anticipate everyproblem that may happend and try to solve it so that faced by the learners. Infact,deviatiom action can be happened anywhere, like in the traditional society in thevillage, in the city or modern society.